Entre a contestação e a superação: a produção camponesa no assentamento rural Tiradentes em Mari. - Souto, Jackson Vital (2007)
The forest zone of Paraíba was always constituted in a privileged space to the advance understanding of the capitalist relations of production in the field and the way the peasant react to this advance, that expropriates them from its condition of peasant. This exactly geographic space was and has been scene of social conflicts, many bloody times, between large estate owners and a population of agricultural workers who search its land piece to guarantee its proper sustenance and conditions of a worthy life. This fight politics has resulted in some relative advances, as the institutionalization of the rural settlement, product of the politics pressure of peasant and landless agricultural workers, organized by the Movement of the Landless Agricultural Workers. This work studies the constitution and the ways of the production organization of the Tiradentes rural settlement, located in the city of Mari and considered the settlement model of the Movement of the Landless - MST in the middle-region of the forest zone of the State of Paraíba. Tiradentes rural settlement was constituted in 2000, into the politics of agrarian reform of the federal government, the Tiradentes gains life after long process of fight whose culminating point was the period of occupation-encampment. After conquering the land and institutionalized the settlement, it was our interest to know the specialities of its productive system, the forms of organizing the production, the canals of commercialization, the relations struck up between the seated peasants and the politics leaderships of the local Movement of the Landless - MST. One of our main finding was that, although the Movement of the Landless Agricultural Workers - MST searches to keep its influence and to lead the settlement through centered goals and national, the seated people follow its proper forms of production searching to preserve, thus, certain autonomy of its condition of being a peasant.